Variation in the Dadanitic inscriptions: the case of RḌY - Kootstra, Fokelien (Proceedings of the Seminar for Arabian Studies, 2019)
In the first millennium BC Dadān was an important oasis town on the incense trading route with a flourishing writing tradition in a local script, called Dadanitic. Dadān (modern-day al-ʿUlā) was situated in the north-west of the Arabian Peninsula. The Dadanitic corpus is the only Ancient North Arabian corpus to boast a substantial number of monumental inscriptions. Despite the official character of these inscriptions, they also contain variation in language, orthography, and technical execution. This paper will focus on the variation in the spelling of the verb from the root √RḌY before enclitic pronouns. It will argue that this particular variation attests a phonological change in the Dadanitic language after it started being written. This has important implications for the orthography and our general understanding of variation in this corpus of inscriptions.